ANALYSIS OF IMPROVEMENT OF NEW ELECTRICITY POWER PLANT BASED ON PALM OIL WASTE - M. Rijal; Hamdani Hamdani; Solly Aryza (Sean Institute, 2022)
Plantation companies that have palm oil processing factories that use their generators as a resource to carry out processing activities and domestic life in the plantation area itself and have their plantations, one of which is the Seiogan mill (SOGM) is a factory that manages palm oil into CPO with a capacity of 60 tons/year. A clock that uses two alternative power sources, namely PLTU Belawan and PLTD. This study discusses the economic feasibility of using PLTU Belawan using the remaining fuel produced by the palm oil mill as a power producer by comparing the use of a generator as a power producer. The steam turbine produces 10 MWh of power when the factory is running. The boiler produces 3 units of steam and operates 2 units of fiber fuel and processed shells. The factory stopped processing resources for employee housing sourced from a generator with a capacity of 500 KVa with diesel fuel. The price of electrical energy for each generator is IDR 22.8 fiber, / Wh shell IDR. 64.5,/k Wh diesel Rp. 732.7,/kWh..